ปัจจัยทำนายคุณภาพชีวิตของผู้ป่วยโรคอารมณ์แปรปรวนสองขั้ว กรุงเทพมหานคร - ณัฐวรา เชื้อหมอ (จุฬาลงกรณ์มหาวิทยาลัย, 2017)
The purposes of this descriptive research were: 1) to study the quality of life in patients with bipolar disorder, Bangkok Metropolis and 2) to determine the predictor of quality of life in patients with bipolar disorders, Bangkok Metropolis; age, education, substance abuse, side effects of antipsychotic drug, depressive symptoms, manic symptoms, social support and symptom self-management. Research subjects were 168 bipolar patients receiving mental health treatments in outpatient department from Faculty of Medicine Siriraj Hospital Mahidol University, Faculty of Medicine Ramathibodi Hospital Mahidol University, Phramongkutklao Hospital and Faculty of Medicine Vajira Hospital Navamindradhiraj University selected by inclusion and exclusion criteria. Research instruments divided into 7 parts which were tested for validity by 5 experts. The reliability of the scales with Chronbach’s alpha were .82, .81, .82, .94, .81 and .84 respectively. Data were analyzed by using mean, SD, and multiple regression. Major findings were as follows: 1. Patients with bipolar disorders, Bangkok Metropilis had score on overall quality of life in the moderate level (x̅ = 84.61). In addition all subscale of quality of life including environment domain, physical domain, psychological domail and social relation domain ( x̅ = 26.50, x̅ = 22.96, x̅ = 19.72, x̅ = 9.06, respectively). 2. Factors significantly predicted quality of life in bipolar patients, Bangkok Metropolis were social support, age, education and depressive symptoms, at the level of .05. These predictors were accounted for 45.2 percent (R2 = .452) The Predictive Standardized Score function was : Zquality of life = .422 age + .155 education – .129depressive symptoms + .484 social support